2015
DOI: 10.1021/acscatal.5b01670
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Hydrogen Oxidation/Evolution Kinetics in Base and Acid by Enhanced Activities at the Optimized Pt Shell Thickness on the Ru Core

Abstract: Hydrogen oxidation and evolution on Pt in acid are facile processes, while in alkaline electrolytes they are two-orders-of-magnitude slower. Thus, developing catalysts that are more active than Pt for these two reactions is important for advancing the performance of anionexchange-membrane fuel cells and water electrolyzers. Herein, we detail a four-fold enhancement in Pt mass activity that we achieved using single crystalline Ru@Pt core-shell nanoparticles with two-monolayer-thick Pt shells, which doubles the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
184
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(193 citation statements)
references
References 43 publications
9
184
0
Order By: Relevance
“…[9][10][11] So far, Pt-based and Ru/Ir-based catalysts have been extensively considered as the most active electrocatalysts for the HER and OER respectively in alkaline media, however, their high costs and source scarcity have limited large-scale production applications. 3,7,[12][13][14] Therefore, searching for cheap, earthabundant and efficient electrocatalysts with high HER and OER activities is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] So far, Pt-based and Ru/Ir-based catalysts have been extensively considered as the most active electrocatalysts for the HER and OER respectively in alkaline media, however, their high costs and source scarcity have limited large-scale production applications. 3,7,[12][13][14] Therefore, searching for cheap, earthabundant and efficient electrocatalysts with high HER and OER activities is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…10 Elbert et al showed that the activation energy increases the most for Volmer reaction from acid to base, leading to a change of rate-determining step from Tafel step in acid to Volmer step in base as well as the shift in optimal HBE from Pt to Ru@Pt catalysts. 11 For HER, besides the adsorption of H ad , the nature of proton donor (either H 3 O + in acid or H 2 O in alkaline) as well the adsorption of OH ad and spectator species were also invoked in explaining the HER activities of different metals in the whole range of pH. 12 The higher HER rate in acid than in base has been explained by the faster formation of H ad from H + than from H 2 O.…”
mentioning
confidence: 99%
“…Finally, as far as HOR is concerned, Adzic and co-workers report increased mass and intrinsic activity at Pt submonolayers/shells deposited on Au or Ru substrates or nanoparticles [79,291] via the galvanic replacement of Cu upd layers.…”
Section: Hydrogen Evolution and Oxidationmentioning
confidence: 99%